Motivations and Performance Conditions for Ethnic Entrepreneurship - Enno Masurel; Peter Nijkamp; Murat Tastan; Gabriella Vindigni (Tinbergen Institute, 2001)
Ethnic entrepreneurship has become a popular concept in a modernmulti-cultural society. This paper seeks to offer an overview of thepotential of ethnic entrepreneurship for solving inter alia thestructural unemployment problems of ethnic groups in cities. Thepresent paper addresses in particular the critical success conditionsfor ethnic entrepreneurs. Based on a survey among ethnicentrepreneurs in the Amsterdam area, the paper sets out to identifyempirically the driving forces for business success, such aseducation or the role of informal networks. The explanatory frameworkdeployed for the identification of these qualitative success factorsfor distinct ethnic groups is based on a particular class ofartificial intelligence methods, viz. rough set analysis. Thismultidimensional classification approach appears to be able toidentify various important factors for the motivation and performanceof ethnic enterprises.
Keywords: 330; Entrepreneurship-Ansatz; Ethnische Gruppe; Niederlande